PENGARUH RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PT. KIMIA FARMA TBK - PUTRI WULANDARI; ALIAH PRATIWI (Universitas Mahasaraswati K. Mataram, 2023)
The stock price is one of the financial benchmarks for a company, with a stable stock price it will also make a company still trusted and in demand by the public. The purpose of this study was to determine the factors that can affect the stock price of PT Kimia Farma Tbk which is listed on the IDX during the 2012-2021 period, especially in the profitability ratios in the form of Return On Assets and Return On Equity of PT Kimia Frma Tbk. The associative approach is the choice in this study. The results showed that in the Partial T test conducted each variable return on assets and return on equity had no effect on stock prices at PT Kimia Farma Tbk. Then the Simultaneous F test shows that all Return On Assets and Return On Equity variables together have no effect on stock prices at PT Kimia Farma Tbk. In conclusion, in this study, it is important for companies to consider many factors in maintaining the stability of stock prices, as an effort to maintain the quality of the company in maintaining public trust as its users.